P54 KIDS-STEP: a swiss multi-centre RCT on effectiveness of adjunct betamethasone therapy in hospitalised children with community acquired pneumonia. Issue 6 (17th May 2019) - Kohns Vasconcelos, M; Santoro, R; Coslovsky, M; van den Anker, J; Bielicki, JA
Abstract : Background: The incidence of community-acquired pneumonia (CAP) in young children is high (20- 30/1000 child-years) and is associated with a high rate of hospitalisation (around 10/1000 child-years). In adults, a benefit of adjunct corticosteroids on time to clinical stability and hospital discharge has been observed and confirmed in systematic reviews and meta-analyses. In contrast, only few small trials have addressed the potential impact of oral steroid treatment in CAP during childhood. The purpose of this study is to concurrently evaluate whether adjunct treatment with corticosteroids in children hospitalised with CAP is more effective in terms of the proportion of children reaching clinical stability and whether such adjunct treatment is no worse in terms of CAP relapse. Methods: Children in KIDS-STEP 1 receive either oral betamethasone or oral placebo dosed once daily for two consecutive days. We include 700 children from age 1 weighing at least 7 kilograms and up to a body weight of 35 kilograms and age below 10 years hospitalised for CAP using a clinical diagnosis. Co-primary outcomes are: (a) The proportion of children clinically stable at 48 hours after randomisation. (b) The proportion of children with CAP-related readmission within 28 days after randomization. Secondary outcomes will be captured to further evaluate the efficacy and safety of adjunct oral steroids in the management of childhood CAP, including proportion of children experiencing solicited side effects of the trial treatment and/or serious adverse events, time to hospital discharge after index hospitalisation in days, time away from routine child care and away from work (for parents) in days up to 28 days after randomisation and total antibiotic exposure in days up to 28 days after randomisation. Results: Enrolment started in November 2018 and is currently proceeding at approximately 1 participant per participating hospital per week. References: Study registration: BASEC - EKNZ 2018–00563 Disclosure(s): Nothing to disclose